PENGARUH MODEL PEMBELAJARAN MASTERY LEARNING BERBANTU GENIALLY TERHADAP HASIL BELAJAR IPAS SISWA KELAS III SDN 68 PALEMBANG - Yenti Adinda, Resti; Aryaningrum , Kiki; Rosmiyati , Evi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The learning outcomes of elementary school students in the subject of IPAS (Science and Social Studies Integration) remain relatively low. One contributing factor is instructional practices that do not adequately address individual differences or utilize engaging media. The Mastery Learning model, which emphasizes complete material mastery through individualized time and assistance, combined with the use of Genially a visual and interactive digital media has the potential to improve student outcomes. This study aims to determine the significant effect of the Mastery Learning model assisted by Genially on the IPAS learning outcomes of third-grade students at SD Negeri 68 Palembang. A quantitative method with a posttest-only control group design was employed. The sample consisted of two classes: the experimental class received instruction using Mastery Learning with Genially, while the control class used conventional teaching methods. A multiple-choice test consisting of 10 items served as the assessment instrument. Results showed that the experimental class achieved a higher posttest mean score (84.5) than the control class (58.75). Additionally, 75% of students in the experimental class were categorized as "very capable," compared to only 20.8% in the control group. The t-test revealed that tcount = 5.653 > ttable = 1.682 with a significance value of 0.000 < 0.05. It is concluded that the Mastery Learning model assisted by Genially significantly improves students’ IPAS learning outcomes by offering adaptive instruction and engaging visual content.